Profiles, Statuses, and Achievements of Female Local Leaders: a Study of the Impact of Direct Local Election - Dewi, Kurniawati Hastuti (Jurnal Perempuan, 2014)
This paper shows that the role and position of Indonesian women in local governance are improving gradually since the implementation of direct elections in 2005. The â€œstructural opportuinitiesâ€ for women to be elected as local leader have increased under the direct elections. The number of women elected as local leaders has risen significantly during 2005-2014 periods. Female local leadersâ€™ profiles are diverse in terms of their socio-political background, individual capital and political parties, reflecting a new typology of female local leaders.The presence of female local leaders does not necessarily mean that they always advocate for women issues in their policy line, as this ideal condition depends on other influential factors. And yet, this paper suggests the declining trend of participation and opportunities of women in local governance as the new Local Government Act No. 23/2014 adopts the election of local government head via the Regional Peopleâ€™s Representative Council to replace the earlier mechanism of direct election.